BUCZKOWSKI BY BARAŃCZAK - Poprawa , Adam (Prace Polonistyczne, 2024)
The article examines texts about Leopold Buczkowski’s experimental prose written by Stanisław Barańczak, an accomplished Polish poet, translator, critic, and scholar of literature. These include several essays, reviews, a conference paper and, most importantly, the master’s thesis that he completed in 1969. Poprawa meticulously reconstructs Barańczak’s interpretations of Buczkowski’s novels, in particular focusing on their textual coherence and cohesion. He notes that Barańczak described characteristic features of Buczkowski’s style in an accurate and innovative way, as well as systematizing stages and trends in the reception of his prose works, based on their commentators’ approaches to the rules of textual coherence and cohesion. The article asks how Barańczak’s texts contribute to Buczkowski studies, why they can be considered canonical, and how the reception of Buczkowski’s oeuvre could have been different had Barańczak’s master’s thesis been published and reached a wider readership.